University Students, Social Media, and Purposeful Use: Networked Knowledge Activities Across Contexts - Dennen, Vanessa; He, Dan (Proceedings of the International Conference on Networked Learning, 2024)
University students are frequent users of networked environments, such as social media, in their everyday lives. Although often associated with socialization and entertainment, their social media use is multifaceted, reaching across other life activities and contexts. This exploratory, qualitative study draws upon interviews with 25 university students in the United States, considering how they use social media across learning and professional contexts, and how they view their role in this setting. During the interviews, students participated in a card sort activity that presented them with 41 potential social media tasks they might engage in as well as two different ways of categorizing social media tasks. Findings showed that students use some social media tools, like Instagram, widely across contexts, while other tools are relegated to specialized use or contexts, largely driven by task. Instructors set the tone for using certain other tools, like X (formerly known as Twitter) or Diigo (a social bookmarking tool), whereas other tools are used to access resources but not to interact, like Pinterest and YouTube. Most students reported using social media to interact with others, but only within well-defined networks comprised of friends and classmates. Interactions with these individuals were focused on supporting friendship and accomplishing learning or extracurricular tasks, respectively. Beyond that, students reported a passive role on social media, consuming rather than producing content and leaving limited traces of their presence in the public sphere, with the exception of situations when students were leaders in extracurricular groups or using social media for their jobs. In those instances, the most common uses were related to posting event and promotional information. After engaging with the social media tasks and activity categories presented in the card sort, students offered two types of reflections. One group reflected on the limited nature of their personal social media use, whereas the other group indicated that there was a range of social media tasks and uses that they had not previously considered. The small group of students who did not offer any sort of post-activity reflection indicated that they had small networks with limited activities by design, and lacked interest in thinking further about them. These findings have implications for higher education institutions, where students might be offered learning, extracurricular, and career support opportunities to help them develop both awareness and skills related to common networked knowledge activities and corresponding digital skills.